Transarterial chemoembolization of hepatocellular carcinoma before liver transplantation and risk of post-transplant vascular complications: a multicentre observational cohort and propensity score-matched analysis. Issue 11 (6th October 2021) - Sneiders, D; Boteon, A P C S; Lerut, J; Iesari, S; Gilbo, N; Blasi, F; Larghi Laureiro, Z; Orlacchio, A; Tisone, G; Lai, Q; Pirenne, J; Polak, W G; et al.
Abstract: Background: Transarterial chemoembolization (TACE) in patients with hepatocellular cancer (HCC) on the waiting list for liver transplantation may be associated with an increased risk for hepatic artery complications. The present study aims to assess the risk for, primarily, intraoperative technical hepatic artery problems and, secondarily, postoperative hepatic artery complications encountered in patients who received TACE before liver transplantation. Methods: Available data from HCC liver transplantation recipients across six European centres from January 2007 to December 2018 were analysed in a 1 : 1 propensity score-matched cohort (TACE versus no TACE). Incidences of intraoperative hepatic artery interventions and postoperative hepatic artery complications were compared. Results: Data on postoperative hepatic artery complications were available in all 876 patients (425 patients with TACE and 451 patients without TACE). Fifty-eight (6.6 per cent) patients experienced postoperative hepatic artery complications. In total 253 patients who had undergone TACE could be matched to controls. In the matched cohort TACE was not associated with a composite of hepatic artery complications (OR 1.73, 95 per cent c.i. 0.82 to 3.63, P = 0.149). Data on intraoperative hepatic artery interventions were available in 825 patients (422 patients with TACE and 403 without TACE). Intraoperative hepatic artery interventions were necessary in 69 (8.4 per cent) patients. In the matched cohort TACE was not associated with an increased incidence of intraoperative hepatic artery interventions (OR 0.94, 95 per cent c.i. 0.49 to 1.83, P = 0.870) Conclusion: In otherwise matched patients with HCC intended for liver transplantation, TACE treatment before transplantation was not associated with higher risk of technical vascular issues or hepatic artery complications. Abstract : Based on a propensity score-matched cohort (297 patients) transarterial chemoembolization before liver transplantation was not associated with an increased incidence of intraoperative hepatic artery (HA) interventions, postoperative HA complications or longer arterialization. Lay Summary: Lay Summary Patients with liver cancer may be treated with transarterial chemoembolization (TACE) during the period on the transplant waiting list. With TACE, chemotherapeutic coils are injected directly into the small arteries supplying the tumour, after which these vessels are closed. The aim of this therapy is to decrease the tumour size and slow down tumour growth. However, concerns are raised that manipulation of the main hepatic artery by TACE may cause damage to the artery itself. If this would result in problems during or after liver transplantation when the artery is connected to the artery supplying the donor liver, this may endanger the donor liver graft survival. The present study shows no increased risk in problems to connect the artery during liver transplantation after TACE treatment. Also, arterial complications after liver transplantation did not occur more frequently if patients had received TACE treatment. The authors therefore conclude that TACE treatment before liver transplantation could be considered a safe approach.